Normovolumetric Haemodilution and Auto Transfusion in Major Operations Prevents Transfusion- Related Complications (Bangladesh Journal of Medical Science, 2022)
Objective: To assess the efficacy and safety normovolumetric haemodilution and auto transfusion in patients undergoing major surgical operations. To compare the outcome differences between normovolumetric haemodilution and auto transfusion with allogenic transfusion group.Methods: The number and intensity of transfusion related complications in 36 patients, who received normovolumetric haemodilution and auto transfusion were compared with 36 patients who received similar amount of allogenic blood in the similar clinical environment and situation. The number and intensity of the complications encountered in study and control groups were compared and evaluated.Results: The study revealed statistically significant reduction in number and frequency of transfusion related complications in the study group comparing with the control group. The study also demonstrated reduction in number and intensity of surgery and anesthesia related complications compared with the control group without detection of harmful effect of haemodilution and auto transfusion. The study group also had statistically insignificant shorter hospital stay comparing with control group.Conclusion: Autologous transfusion with normovolemic haemodilution appears to be a safe and feasible method of reducing the need for homologous transfusion. Transfusion-related complications were significantly fewer in the autotransfusion group in comparison with allotransfusion, in patients undergoing major operations.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 547-552